2019
DOI: 10.1021/acs.langmuir.9b01600
|View full text |Cite
|
Sign up to set email alerts
|

Initial Growth Study of Atomic-Layer Deposition of Al2O3 by Vibrational Sum-Frequency Generation

Abstract: The initial growth during the atomic-layer deposition (ALD) of Al 2 O 3 using trimethylaluminum (TMA) and water was studied on two starting surfaces: SiO 2 and −H-terminated Si(111) [H/Si(111)]. In situ spectroscopy ellipsometry (SE) showed virtually immediate growth of Al 2 O 3 on both surfaces, although for H/Si(111) a reduced growth-per-cycle was observed in the initial 20 cycles. The underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…One mechanism may be due to a low reactivity of the (heavy) water with surface −CH 3 ligands, which has been proposed to be one of the main limiting factors in the GPC at low temperatures. 41 Vandalon et al have shown there is a persistent amount of −CH 3 surface groups after the H 2 O pulse, which significantly decrease by increasing the deposition temperature higher than 250 °C. 41 Shirazi et al have also shown through DFT calculations the persistency of methyl ligands after a water pulse.…”
Section: ■ Resultsmentioning
confidence: 99%
“…One mechanism may be due to a low reactivity of the (heavy) water with surface −CH 3 ligands, which has been proposed to be one of the main limiting factors in the GPC at low temperatures. 41 Vandalon et al have shown there is a persistent amount of −CH 3 surface groups after the H 2 O pulse, which significantly decrease by increasing the deposition temperature higher than 250 °C. 41 Shirazi et al have also shown through DFT calculations the persistency of methyl ligands after a water pulse.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In the literature, it is very popular to use the exponential function to represent the ALD reactions. [36][37][38] However, for the exponential function, the slope (absolute value) monotonously decreases to zero. Some ALD reactions experience an initial growth delay due to the surface effect.…”
Section: Three-effect Modelmentioning
confidence: 99%
“… 29 With BB-SFG spectroscopy, the functional groups present on the surface during ALD can be identified and the (relative) density of surface groups can be followed in situ , as is illustrated by our earlier work monitoring the density of CH 3 , OH, and Si–H groups during ALD of Al 2 O 3 . 30 32 Identification of the hydrocarbon species on the surface of the precursor is of particular interest for the Pt ALD process and, therefore, the CH stretch region of the IR spectrum was probed with BB-SFG spectroscopy. Apart from identifying surface groups, the reaction kinetics during the precursor half-cycle and the influence of temperature on the surface chemistry were also studied.…”
Section: Introductionmentioning
confidence: 99%